Assessing the Organizational Impact of Development Cooperation: a Case from Agricultural R&D - Horton, Douglas; Mackay, Ronald (International Service for National Agricultural Research, 1998)
This paper reports on an evaluation of the organizational impacts of the International Service for National Agricultural Research. ISNAR is a non-profit agency with a mandate is to strengthen national agricultural research organizations and systems. For the purposes of this study, organizational impacts are defined as the effects of ISNAR's activities and outputs on the external environment, organizational motivation and capacity of client organizations. The paper outlines the context and objectives of the evaluation and the conceptual framework developed for it. A set of component evaluation studies, data collection and analysis procedures and some salient findings are described. Overall results are contrasted with the initial evaluation objectives.